Penal liability arising from the publication of bad content - Hasan Al-Tamimi, Assist. Lect. Noor (Basra studies journal, 2024)
Recently, the internet has become an accessible medium for the flow and dissemination of information, serving as a launch point for education, cultural awareness, and freedom of expression. While the ideas transmitted through the internet largely aim to satisfy legitimate informational needs, there is another aspect that can involve numerous deviations, such as the dissemination of images, symbols, and information harmful to individuals and society at large. These publications constitute a set of unlawful and unethical practices. In the research titled " Penal liability arising from the publication of bad content," it is evident that the Iraqi legislator, through the current Penal Code, specifically in articles 403 and 404, addresses the criminal liability associated with content publication. The law stipulates that the publication of images, symbols, films, and the open expression of obscene songs or statements are all behaviors punishable by law if they violate public decency and morals. The Iraqi legislator has given public taste the authority to determine what constitutes bad content, which poses a problem as the legislator did not establish a precise standard to differentiate bad content from quality content.